2011
DOI: 10.3892/etm.2011.275
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a family history of breast and/or ovarian cancer on breast cancer outcomes

Abstract: Abstract. Various published studies have been inconclusive in attempting to relate a family history of breast and/or ovarian cancer (BOC) to the survival of breast cancer patients. The aim of the study was to investigate the association of a family history of BOC with tumor characteristics, treatment response and the difference between the prognosis of familial breast cancer (FBC) patients and sporadic breast cancer (SBC) patients. Data on 348 operable FBC patients and 345 SBC patients were retrospectively ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A systematic review 4 published in 1999 summarized evidence on the association between family history of BC and BC prognosis and concluded that conflicting data existed, mostly due to small samples. Since then, studies with larger samples 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 have been conducted; however, these studies had mixed findings, with some reporting worse prognosis among those with a family history of BC, 5 , 6 , 7 some finding no significant difference, 8 , 9 , 10 , 11 , 12 and some reporting that family history had a protective benefit for prognosis. 13 , 14 , 15 Even less is known about whether the association differs across BC subtypes, such as ER-positive and ER-negative BC.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review 4 published in 1999 summarized evidence on the association between family history of BC and BC prognosis and concluded that conflicting data existed, mostly due to small samples. Since then, studies with larger samples 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 have been conducted; however, these studies had mixed findings, with some reporting worse prognosis among those with a family history of BC, 5 , 6 , 7 some finding no significant difference, 8 , 9 , 10 , 11 , 12 and some reporting that family history had a protective benefit for prognosis. 13 , 14 , 15 Even less is known about whether the association differs across BC subtypes, such as ER-positive and ER-negative BC.…”
Section: Introductionmentioning
confidence: 99%
“…The participants of the current study were healthy people through the family history record of three types of tumor [4]. The current research goal was to identify coping styles that remain detrimental to subjective stress adaptation and to identify more good adaptation styles by exploring the association among cancer family history, coping style, and psychological pain that will offer respected data for psychological health meddling [5].…”
Section: Introductionmentioning
confidence: 99%